Capital Mobility vs. Labor Mobility:Theory and Implications - Song, Garrison Hongyu (International Journal of Economics and Financial Issues, 2022)
A random search-based model is proposed to study the impact of the relative mobility of capital with respect to labor on income inequality and financial globalization for the first time. Our simulation results indicate that capital is less mobile than labor domestically. Our simulation results further suggest the duality of capital mobility in financial globalization, in which more mobile capital may not always promote financial globalization. Lastly, our simulation results show that the share of labor income in the gross proceeds is negatively related to the relative mobility of capital, the separating rate between capital and labor, and the bargaining power of capital, which may shed light on income inequality in the U.S.